Improvements in ionospheric forecasting capability - Rush, C. M. (Charles M.); Air Force Cambridge Research Laboratories (U.S.) (L.G. Hanscom Field, Bedford, Massachusetts : Air Force Cambridge Research Laboratories, Air Force Systems Command, United States Air Force, 1972)
The results of a study undertaken to determine the feasibility of employing synoptic mapping to improve ionospheric forecasting capabilities are presented. Using electron density data obtained from 16 ionosonde stations located in North America and Greenland during the time period mid-April through July 1970, the temporal and spatial variability of the ionosphere was assessed. (Author).
Research supported by the Air Force Cambridge Research Laboratories, Air Force Systems Command, United States Air Force, L.G. Hanscom Field, Bedford, Massachusetts.
Ionospheric Physics Laboratory Project ILIR.
AD0742258 (from http://www.dtic.mil).
"28 February 1972."
Includes bibliographical references (pages 55-56).
Mode of access: Internet.
Keywords: Radio -- Interference; Magnetic storms; Ionospheric radio wave propagation; Ionospheric forecasting; Electron distribution; Radio -- Interference; Electron distribution; Magnetic storms; Ionospheric radio wave propagation; Ionospheric forecasting